The death spiral of coal in the USA: Will new U.S. energy policy change the tide? - Roman Mendelevitch; Christian Hauenstein; Franziska Holz (Deutsches Institut für Wirtschaftsforschung (DIW), 2019)
The Trump administration has promised to stop the spiraling down of the U.S. coal industry that has been going on for several years. We discuss the origins of the decline of the U.S. coal industry and new policy interventions by the Trump administration. We find that a further decrease of coal consumption in the U.S. electricity sector must be expected because of the old and inefficient U.S. coal-fired generation fleet. By contrast, we adapt the EIA's overly optimistic view and analyze three potential support schemes to assess whether under such assumptions they can turn the tide for the U.S. coal industry: i) revoking the Clean Power Plan (CPP); ii) facilitating access to the booming Asian market by developing West Coast coal export terminals; and iii) enhanced support for the Carbon Capture, Transport and Storage (CCTS) technology to provide a long-term perspective for domestic coal use while mitigating climate change. We investigate the short-term and long-term effects for U.S. coal production using a comprehensive partial equilibrium model of the world steam coal market, COALMOD-World (Holz et al. 2016). Revoking the CPP will stop the downward trend of steam coal consumption in the U.S., but will not lead to a return of U.S. coal production to the levels of the 2000s with more than 900 Mtpa. Even when assuming a continuously strong global coal demand and expanding U.S. coal export capacities, U.S. coal production will not return to its previous production highs. When global steam coal use, including U.S. consumption, is aligned with the 2°C climate target, U.S. steam coal production drops to around 100 Mtpa by 2030 and below 50 Mtpa by 2050, respectively, even if CCTS is available and exports via the U.S. West Coast are possible.
Keywords: L72; Q34; Q38; F14; 330; U.S. coal sector; Trump administration; Clean Power Plan; steam coal; coal ports; CCS